Bacterial secondary metabolites : synthesis and applications in agroecosystem - Abd-Elsalam, Kamel A.; Mohamed, Heba I. (Nanobiotechnology for plant protection, 2023)
Bacterial Secondary Metabolites: Synthesis and Applications in Agroecosystem presents the structure, properties, and biotechnological applications of bacterial metabolites and their upcoming industrial, pharmaceutical, antimicrobial, and anticancer applications. Chapters cover topics such as the use of lactic acid bacteria as an antifungal and antibacterial agent, bacterial siderophores structure and potential applications, and the role of cyanobacteria metabolites in disease management, amongst others. Plant and agri-food environmental scientists and researchers, graduate, and post-graduate students in related fields will benefit from this reference book which is published as part of the Nanobiotechnology for Plant Protection series.